A Brief Analysis of Smart Contracts and Applications of Blockchain Technology - Matura, Rishi; Kunal (Journal of Artificial Intelligence and Capsule Networks, 2023)
Blockchain refers to a distributed system or ledger that is shared via a computer network. For storing data, a blockchain serves as a digital database. The most well-known use of Blockchain technology is to maintain a secure and impartial record of every transaction made using Bitcoin and other types of cryptocurrency. By assuring the security and integrity of a data record, a blockchain encourages confidence without the need for a trustworthy third party. This paper discusses the various aspects and implications of Blockchain technology in modern society.
Keywords: Blockchain; system; database; digital; cryptocurrency; Bitcoin; smart contract